ANALISIS PERAN SEKRETARIAT DEWAN (SETWAN) DPRD KOTA SUNGAI PENUH BERDASARKAN UNDANG-UNDANG KETERBUKAAN INFORMASI PUBLIK: Badrizal - M.Si, Badrizal, (Qawwam : The Leader's Writing, 2020)
In preliminary obsevations, the researcher was interested in knowing how and to what extent the role of the Sungai Penuh government, especially the secretariat of the Sungai Penuh DPRD council, in implementing law number 14 of 2008, regarding publik information disclosure. The approach used in this research is qualitative. Data collection techniques and tools in this study were interviews, observatioan and documentation. Data collection tools in the form of questionnaires, pen, books/paper, recording devices. The unit of analysis is individual officers and staff at the DPRD Secretariat of Sungai Penuh city. Here the researcher wants to know the extent of the role of the Secretariat of the Council in providing information services to the public, whether it is running well or not. Where Law number 14 of 2008, demands and obliges state administrators to give the public the right to obtain information on every activity organized by the organizer or a state institution. To get the title of best servant, of course, state officials must carry out activities in accordance with the applicable rules and regulations.